Interpreting Japan's contested memory: Conservative and progressive traditions. (September 2015) - Dian, Matteo
This article applies an interpretive approach to account for the process of definition and contestation over wartime memory in Japan. It first locates the role of memory in interpretive theory, emphasising how beliefs about the past are a crucial component of foreign policy traditions. Second, it highlights how the process of contestation over a country's memory is fundamentally intertwined with attempts to legitimise or resist key foreign policy decisions in response to contemporaneous dilemmas that force a confrontation with historical traditions. This is illustrated through an analysis of the Yoshida Doctrine's problematic compromise between conservative and progressive traditions of thought about Japan's role in the Second World War, beginning with the period of US Occupation, moving through the Cold War years and ending with the death of the Shōwa Emperor in 1989. Finally, it studies the 'normalisation' of Japanese foreign policy during the post-Cold War Heisei period, the dilemmas caused by the debate over wartime memory and the effort to achieve reconciliation with other Asian nations. The central argument is that post-war Japanese foreign policy has generally represented an uneasy and evolving compromise between the conservative and progressive traditions.